Social work the basics - Doel, Mark 1950- (The basics, 2023)
This revised second edition of Social Work: The Basics is an insightful introduction to the often misrepresented world of social work. This accessible book presents a broad view of contemporary social work, exploring its roots and its possible future. It dispels myths surrounding social work, addresses media debates, and offers a balanced account of what social workers do. Drawing examples from the full range of social work practice, this book is valuable reading for all individuals interested in the field of social work. It will provide a helpful introduction for students considering a career in social work, those beginning social work courses, and other professionals whose work brings them into contact with social workers"--